Feed additives for swine: Fact sheets – prebiotics and probiotics, and phytogenics - Jacela, Jay Y.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Renter, David G.; Dritz, Steven S. (My University, 2012)
There is increasing pressure for livestock producers to minimize the use of antibiotics as growth promoters in food animals. Supplementing benefi cial microorganisms in the gastrointestinal tract is one potential alternative. A diverse population of benefi cial and potentially harmful microorganisms exists in the gastrointestinal tract of the pig. In a healthy animal, a delicate balance between these two groups of organisms is maintained. However, during times of stress, such as during weaning in the case of piglets, this balance may be affected and can lead to a rapid growth of harmful microorganisms. This may result in poor performance or disease. Thus, prebiotics and probiotics have been the subject of much research over the years as potential replacements for antibiotic growth promoters in pigs.Restriction on the use of in-feed antibiotics in many countries has fueled the interest in alternative products. A group of natural products known as phytogenics has been the focus of several studies in recent years. Also referred to as phytobiotics or botanicals, phytogenics are plant-derived products used in feed to potentially improve pig performance. Aside from having antimicrobial activity, these products potentially provide antioxidative effects, enhance palatability, improve gut functions, or promote growth. However, there is limited research validating their potential benefits for pigs.
Keywords: Swine; Feed additives; Prebiotics; Probiotics; Phytogenics; Growth